Technology, Media Literacy, and the Human Subject - S. Lewis, Richard (Open Book Publishers, 2021)
We are mediated by and immersed in a world where information and communication technologies (ICTs) are undergoing accelerated innovation. From hardware like smartphones, smartwatches, and home assistants to software like Facebook, Instagram, Twitter, and Snapchat, our lives have become inextricably entwined with a complex, interconnected network of relations. Scholarship on media literacy has tended to focus on developing the skills to access, analyse, evaluate, and create media messages without considering or weighing the impact of the technological medium and the broader context.